PENGARUH BRAND AMBASSADOR DAN KOREAN WAVE TERHADAP BRAND IMAGE DAN KEPUTUSAN PEMBELIAN - Ningsih, Rika Widia; Wijayanto, Gatot; Marhadi, Marhadi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The phenomenon of the Korean Wave which created fanatical fans indirectly also shaped the lifestyle of the fans themselves. In this phenomenon, Korean Wave fans consume a cultural product. Korean culture has been exposed all over the world. This study aims to determine the effect of Brand Ambassador and Korean Wave on Brand Image and Purchase Decision of Nature Republic Brand at Pekanbaru city. The study was conducted on Nature Republic consumers who live in the city of Pekanbaru by distributing questionnaires to 112 respondents as samples. The sampling technique used in this study is non-probability sampling. Data analysis method using Structural Equation Modeling- Partial Least Square (SEM-PLS) using Warp-PLS software version 6.0. The results of the research show that Brand Ambassador and Korean Wave have a significant effect on Brand Image. Brand Image, Brand Ambassador, and Korean Wave have a significant effect on purchasing decisions. Brand Ambassador and Korean Wave have a significant effect through Brand Image on Brand Nature Republic at Pekanbaru city.